Redox-Active Bisphosphonate-Based Viologens as Negolytes for Aqueous Organic Flow Batteries - Gonzalez, Gabriel; Nechaev, Anton A.; Peshkov, Vsevolod A.; Martínez-González, Eduardo; Belyaev, Andrey; Hamza, Andrea; Shahsavan, Mahsa; Pihko, Petri M.; Peljo, Pekka (Wiley-VCH Verlag GmbH & Co. KGaA, 2025)
Viologen derivatives feature two reversible one-electron redox processes and have been extensively utilized in aqueous organic flow batteries (AOFBs). However, the early variant, methyl viologen (MVi), exhibits low stability in aqueous electrolytes, restricting its practical implementation in AOFB technology. In this context, leveraging the tunability of organic molecules, various substituents have been incorporated into the viologen core to achieve better stability, lower redox potential, and improved solubility. In this work, we introduce bisphosphonate-substituted viologens (BBPE−Vi and MBPE−Vi) as candidates for AOFBs. The bulkiness and negative charges of the bisphosphonate groups enhance the solubility and the electrostatic repulsion among viologen molecules, minimizing the bimolecular side reactions that lead to degradation. Additionally, the electron-rich character of this new substituent in its deprotonated state significantly lowers the redox potential. As a result, the proposed viologen derivatives exhibit high solubility (1.45 M in water) and stability (capacity decay of 0.009 %/cycle or 0.229 %/day when tested at 0.5 M). These parameters are coupled with the lowest redox potentials exceeding all previously reported viologens utilized in AOFBs (−0.503 V and −0.550 V against SHE for MBPE−Vi and BBPE−Vi, respectively).